2020
DOI: 10.1177/1059601120901619
|View full text |Cite
|
Sign up to set email alerts
|

Does Servant Leadership’s People Focus Facilitate or Constrain Its Positive Impact on Performance? An Examination of Servant Leadership’s Direct, Indirect, and Total Effects on Branch Financial Performance

Abstract: Servant leadership’s positive effects for employees and the organization are well-documented, but servant leadership theory postulates that servant leaders prioritize people more than production. This untested supposition raises questions about whether servant leadership’s emphasis on employee support relative to goal achievement has negative consequences for a unit’s financial performance through group organizational citizenship behavior (OCB) that constrain servant leadership’s positive effect on un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 82 publications
0
27
0
Order By: Relevance
“…As servant leadership highlights the serviceoriented activities in the workplace [3], scholars have continuously suggested that servant leadership plays a critically important role in managerial activities in the service industry [3,27]. Specifically, servant leadership theory postulates that servant leaders prioritize people more than production [28], which can help service employees relieve their stress and negative emotion during working hours By focusing on whether and how servant leadership contributes to employees' COB, we aim to make several contributions to the literature. First, we extend the COB research by incorporating possible influence exerted by servant leaders in stimulating employees' COB, which responds to scholars' call for research gauging the impact of servant leadership on diverse employees' desirable outcomes from a broad perspective.…”
Section: Research Background and Theoretical Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As servant leadership highlights the serviceoriented activities in the workplace [3], scholars have continuously suggested that servant leadership plays a critically important role in managerial activities in the service industry [3,27]. Specifically, servant leadership theory postulates that servant leaders prioritize people more than production [28], which can help service employees relieve their stress and negative emotion during working hours By focusing on whether and how servant leadership contributes to employees' COB, we aim to make several contributions to the literature. First, we extend the COB research by incorporating possible influence exerted by servant leaders in stimulating employees' COB, which responds to scholars' call for research gauging the impact of servant leadership on diverse employees' desirable outcomes from a broad perspective.…”
Section: Research Background and Theoretical Discussionmentioning
confidence: 99%
“…As servant leadership highlights the service-oriented activities in the workplace [3], scholars have continuously suggested that servant leadership plays a critically important role in managerial activities in the service industry [3,27]. Specifically, servant leadership theory postulates that servant leaders prioritize people more than production [28], which can help service employees relieve their stress and negative emotion during working hours [3]. In this regard, servant leadership is different from other HR actives and leadership approaches (e.g., empowering leadership).…”
Section: Research Background and Theoretical Discussionmentioning
confidence: 99%
“…We adapted four items from Ehrhart (2004) to measure daily perceptions of servant leadership. Ehrhart's (2004) operationalization has been widely used (Adiguzel et al, 2020;Hartnell et al, 2020;Neubert et al, 2016;Walumbwa et al, 2010;Yang et al, 2017) and represents one of the two most prominent measures with high similarity to the measure by Liden et al (2008;Lemoine et al, 2019). The scale encompasses seven behavioral categories (i.e., forming relationships with subordinates, empowering subordinates, helping subordinates grow and succeed, behaving ethically, having conceptual skills, putting subordinates first, and creating value for those outside of the organization) that are combined into one overall servant leadership construct.…”
Section: Daily Servant Leadershipmentioning
confidence: 99%
“…Servant leadership has service as a first priority, focuses on listening to employees, self-awareness in the leader and considers how to think about others, situations and organisations. It is this moral (Lemoine, et al , 2019) and ethical (Hartnell et al , 2020) position, that is focused on others, and characterised by trust, fairness and high-quality relationships (Lee et al , 2019), that is at the heart of servant leadership. Two meta-analyses demonstrate servant leadership as an evidence-based leadership approach, with predictive validity above and beyond transformational leadership (Hoch et al , 201) and authentic and ethical leadership (Lemoine et al , 2019).…”
Section: Defining Servant Leadershipmentioning
confidence: 99%
“…Moreover, servant leaders have as their primary concern, the growth of employees, the consumer stakeholders, and then the organisation and the bottom line. Hartnell et al (2020) suggest that servant leaders do have task achievement as an ethical and moral obligation to all stakeholders. But, it is the care and involvement of employees that takes precedence, many organisational outcomes are indirectly impacted by this type of leadership approach (Eva et al , 2020; Lee et al , 2019; Parris and Peachy, 2012).…”
Section: Defining Servant Leadershipmentioning
confidence: 99%